Annual Bands in Vertebrae Validated by Bomb Radiocarbon Assays Provide Estimates of Age and Growth of Whale Sharks - Ong, Joyce J. L.; Meekan, Mark G.; Hsu, Hua Hsun; Fanning, L. Paul; Campana, Steven E. (Frontiers in Marine Science, 2020)
Conservation and management strategies for endangered and threatened species require accurate estimates of demographic parameters such as age and growth. The whale shark, Rhincodon typus, is the largest fish in the world and is highly valued in the eco-tourism sector. Despite conservation concerns and advances in our understanding of their life history, basic demographic parameters for growth, longevity and mortality are of questionable accuracy; previous growth studies could not agree whether the vertebral growth bands were formed annually or biannually. Here, we provide the first validation of the annual formation of growth bands within the vertebrae of the whale shark using bomb radiocarbon assays. Ages of up to 50 years were estimated from sectioned vertebrae of sharks collected in Taiwan and Pakistan. There was no cessation of the formation of growth bands in the vertebrae of older sharks and our study provides the oldest observed longevity for this species. Initial estimates of growth (k = 0.01–0.12) and natural mortality rates (M = 0.09–0.14) are consistent with those expected of long-lived sharks, which highlights their sensitivity to fishing pressure and conservation concerns.